PSYCHOLOGICAL CONTENT AND FACTORS OF LONELINESS OF THE PERSONALITY - Kolomiіets, Lesia; Hryhoruk, Evgeniia (PSYCHOLOGICAL JOURNAL, 2017)
The article deals with psychological content and factors of loneliness of the individual. The authors pay attention to the contradictions on the theoretical and empirical levels of perception of this phenomenon, and the need for its translation to the rank relevant to the modern scientific perception. The problem of loneliness is considered from the point of view of various approaches as in the negative (destructive factor in the development of the individual) and positive (a necessary stage of self-acceptance and self-understanding) aspects. A negative connotation of loneliness signs in scientific publications representatives of the psychodynamic, interaccounting, cognitive, sociological and phenomenological approaches. At the same time, a kind of positive assessment of the state of loneliness can be traced in timescom and existential-humanistic approaches. The authors identify two groups of factors that provoke loneliness, individually-psychological (anxiety, locus of control, identity, communicative competence, self-concept, social and emotional intelligence, character traits, reflection, level of aspiration, psychological defense mechanisms, coping strategies, self-hypnosis, self-esteem and introversion, empathy, detachment), and socio-psychological (rejection by a group, the reorientation of communication, the rupture of friendly and/or romantic relationships, no social circle, and limitations of intimate manifestation). In the article the components of the experience of loneliness are analyzed: cognitive (alienation, identity), emotional (acceptance, rejection), behavioral (solitude, alienation, isolation), motivational and volitional (self-realization, derealization). On the basis of a detailed analysis of theoretical sources we show the types of loneliness: the level of human interaction with the environment (physical or spatial, communicative and spiritual, cultural); duration in time (episodic and chronic); by origin (voluntary and involuntary, disturbing, social, emotional); behavioral manifestations (diffuse, accugauge, disociada). We developed a schematic model, the most convenient for theoretical generalizations and further empirical verification. Authors also have made scientific discourse allows one to identify characteristics of the psychological phenomenon of loneliness, to build on this basis, the author’s holistic perspective of its perception.